Customer relationship management : concept, strategy, and tools - Kumar, V.; Reinartz, Werner (Berlin : Springer, 2018)
This book presents an extensive discussion of the strategic and tactical aspects of customer relationship management as we know it today. It helps readers obtain a comprehensive grasp of CRM strategy, concepts and tools and provides all the necessary steps in managing profitable customer relationships. Throughout, the book stresses a clear understanding of economic customer value as the guiding concept for marketing decisions. Exhaustive case studies, mini cases and real-world illustrations under the title "CRM at Work" all ensure that the material is both highly accessible and applicable, and help to address key managerial issues, stimulate thinking, and encourage problem solving. The book is a comprehensive and up-to-date learning companion for advanced undergraduate students, master's degree students, and executives who want a detailed and conceptually sound insight into the field of CRM. The new edition provides an updated perspective on the latest research results and incorporates the impact of the digital transformation on the CRM domain.
CRM: Conceptual Foundation: Strategic CRM Today -- Concepts of Customer Value -- Strategic CRM: Strategic CRM -- Implementing the CRM Strategy -- Analytical CRM: Customer Analytics Part I -- Customer Analytics Part II -- Data Mining -- Using Databases -- Operational CRM: Software Tools and Dashboards -- Loyalty Programs: Design and Effectiveness -- Campaign Management -- Impact of CRM on Marketing Channels -- CRM Issues in the Business-To-Business Context -- Customer Privacy Concerns and Privacy Protective Responses -- CRM in Social Media -- Advances in CRM Applications: Applications of CRM in B2B and B2C Scenarios Part II -- Future of CRM.
Description based on publisher-supplied MARC data.
Keywords: Marketing. Distribution of products; Big data; Customer relations-Management.; Leadership; Customer Relationship Management; Big Data/Analytics.; Business Strategy/Leadership.